BOOTSTRAPPING ANALYSIS OF FACTORS AFFECTING RELIGIOUS MODERATION IN MEDAN CITY - Hasan Sazali; Abdul Rahman Matondang (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This study aims to analyze the influence of religiosity, religious tolerance, and communication that directly and indirectly affects Religious Moderation in Medan City. This study uses a quantitative method with bootstrapping analysis using the Smart PLS3.01 application. Respondents in this study were Muslims in Medan City aged 17-45 years who were drawn based on the Slovin formula with a significance degree of 0.10. The sample of this study amounted to 100 people determined by proportional random sampling, which was drawn evenly based on the population of Medan City per sub-district. The results of this study show that religiosity and religious tolerance directly affect religious moderation in Medan City. The communication variable as an intervening variable failed to indirectly influence religiosity and religious tolerance on religious moderation in Medan City. The recommendations are: Religious moderation needs to be a solution amid the problems of intolerance and disintegration in Medan by promoting effective communication. Values in religious moderation are still too general and abstract to be applied in various regions with different cultural conditions and styles. For that, we need a local formulation to implement how religious moderation works, Further research is needed on aspects of local culture to strengthen moderation in Medan City.